2013
DOI: 10.1042/bj20121518
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor activator inhibitor type 2 (HAI-2) modulates hepcidin expression by inhibiting the cell surface protease matriptase-2

Abstract: Matriptase-2, a recently identified cell surface protease, is the key enzyme of iron homoeostasis modulating the expression of the liver peptide hormone hepcidin. HAI (hepatocyte growth factor activator inhibitor) types 1 and 2 (HAI-1 and HAI-2 respectively) have been shown to inhibit the close homologue, i.e. matriptase. By co-expressing matriptase-2 and the inhibitor HAI-2 we have identified HAI-2 displaying high inhibitory potential against matriptase-2 at the cell surface as well as in conditioned medium. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 46 publications
3
30
0
Order By: Relevance
“…However, this does not rule out the involvement of other molecules in this process. For example, a recent study showed that the hepatocyte growth factor activator inhibitor-2 (HAI-2), a serine protease inhibitor, can form a complex with MT2 to inhibit its enzymatic activity, which indirectly increases the hepcidin expression in hepatic cell lines (48). HAI-2 is a type I transmembrane glycoprotein with two Kunitz-type serine protease domains in their extracellular portion (49 -52).…”
Section: Discussionmentioning
confidence: 99%
“…However, this does not rule out the involvement of other molecules in this process. For example, a recent study showed that the hepatocyte growth factor activator inhibitor-2 (HAI-2), a serine protease inhibitor, can form a complex with MT2 to inhibit its enzymatic activity, which indirectly increases the hepcidin expression in hepatic cell lines (48). HAI-2 is a type I transmembrane glycoprotein with two Kunitz-type serine protease domains in their extracellular portion (49 -52).…”
Section: Discussionmentioning
confidence: 99%
“…With 35% identity and structural similarities with matriptase-1 (Velasco et al, 2002), it is possible that matriptase-2 is also associated with an endogenous inhibitor. Indeed, Maurer et al (2013) recently demonstrated that HAI-2 is a cognate inhibitor of matriptase-2 that inhibits its proteolytic activity, and thus increases hepcidin expression in vitro . However, the physiological role of HAI-2 in the regulation of hepcidin and iron metabolism remains to be investigated.…”
Section: Biochemistry Of Matriptase-2mentioning
confidence: 99%
“…Other groups report that the transcription of the MT2-encoding gene TMPRSS6 can be upregulated either by BMP6 through the BMPsignaling pathway (55) or by hypoxia through both HIF-1α and HIF-2α (56,57). Additionally, a recent study showed that hepatocyte growth factor activator inhibitor type 2 (HAI-2) can form a complex with MT2 to inhibit the enzymatic activity of MT2, which indirectly influences the expression of hepatic hepcidin (58). Despite these important observations, the precise mechanism for the regulation of MT2 expression by iron remains to be elucidated.…”
Section: Control Of Hepcidin Expressionmentioning
confidence: 99%